Extra‐nigral pathological conditions are common in Parkinson's disease with freezing of gait: An in vivo positron emission tomography study. Issue 9 (7th June 2014) - Bohnen, Nicolaas I.; Frey, Kirk A.; Studenski, Stephanie; Kotagal, Vikas; Koeppe, Robert A.; Constantine, Gregory M.; Scott, Peter J.H.; Albin, Roger L.; Müller, Martijn L.T.M.
Abstract Cholinergic denervation has been associated with falls and slower gait speed and β‐amyloid deposition with greater severity of axial motor impairments in Parkinson disease (PD). However, little is known about the association between the presence of extra‐nigral pathological conditions and freezing of gait (FoG). Patients with PD (n = 143; age, 65.5 ± 7.4 years, Hoehn and Yahr stage, 2.4 ± 0.6; Montreal Cognitive Assessment score, 25.9 ± 2.6) underwent [11C]methyl‐4‐piperidinyl propionate acetylcholinesterase and [11C]dihydrotetrabenazine dopaminergic PET imaging, and clinical, including FoG, assessment in the dopaminergic "off" state. A subset of subjects (n = 61) underwent [11C]Pittsburgh compound‐B β‐amyloid positron emission tomography (PET) imaging. Normative data were used to dichotomize abnormal β‐amyloid uptake or cholinergic deficits. Freezing of gait was present in 20 patients (14.0%). Freezers had longer duration of disease (P = 0.009), more severe motor disease (P < 0.0001), and lower striatal dopaminergic activity (P = 0.013) compared with non‐freezers. Freezing of gait was more common in patients with diminished neocortical cholinergic innervation (23.9%, χ2 = 5.56, P = 0.018), but not in the thalamic cholinergic denervation group (17.4%, χ2 = 0.26, P = 0.61). Subgroup analysis showed higher frequency of FoG with increased neocortical β‐amyloid deposition (30.4%, Fisher Exact test: P = 0.032). Frequency of FoG was lowest with absence of both pathological conditions (4.8%), intermediate in subjects with single extra‐nigral pathological condition (14.3%), and highest with combined neocortical cholinopathy and amyloidopathy (41.7%; Cochran‐Armitage trend test, Z = 2.63, P = 0.015). Within the group of freezers, 90% had at least one of the two extra‐nigral pathological conditions studied. Extra‐nigral pathological conditions, in particular the combined presence of cortical cholinopathy and amyloidopathy, are common in PD with FoG and may contribute to its pathophysiology. © 2014 International Parkinson and Movement Disorder Society